دراسة التأثيرات السمية الخلوية للمستخلص المائي لبذور الحلبة ومعقد البلاديوم (II) الجديد على الخط الخلوي لسرطان امعاء الفئران في العراق - عبد الرزاق ايمان هاشم (Al-Nahrain Journal of Science, 2018)
treat arthritis inflamed lungs, diabetes, etc. Numerous palladium complexes with promising activity against tumor cell lines have been synthesized. This study involved the evaluation of Aqueous Fenugreek seeds Extract and new palladium (II) Complex with general formula [Pdl2].2ETOH, where L=2-hydroxy phenyl piperonalidine have a promising anitcancer effect on growth cancer cells and were compared to the anti cancer drug cis-ptatinum by utilizing an in vitro system in femal Balb/c mice by using the Inhibitor Rate as a parameter for the cytotoxic effects on Intestine cancer cell line L20B. Cancer cells were treated with four concentrations of cis-platin 31.25,62.5,125, and 250 μg/ml for 48 and 72 hours .The same concentrations were used for the other extract and complex. This study showed that extract and [PdL2]. 2EtOHcomplex have a promising anti cancer cells as could be seen from these effect on Increased of Inhibition cancer cells at different concentrations and these effect were similar to the effect of cis- platin, then the Inhibitory Rate was increased to 44.60,52.32% and 37.93, 42.97% in cancer cells treated with 250 μg/ml of palladium (II) complex and extract respectively on hours exposure with not singnificant differences with compared Cis- platin.